3 STEMI care in octogenarians and nonagenarians: a 5-year review from an Irish PPCI centre. (16th October 2019) - Connor, CO; Kumar, R; Chongprasertpon, N; Buckley, A; Kumar, J; Murphy, L; Arnous, S; Kiernan, T
Abstract : Introduction: At present, relatively little is known about the outcomes of STEMI in the octogenarian and nonagenarian populations as they have been under-represented in previous studies. An increasing population of elderly patients with risk factors for CAD has resulted in an increase in the number of elderly patients presenting with ST elevation myocardial infarction (STEMI). The acute management of patients >80 years with STEMI is fraught with difficulty due to a higher risk from STEMI alongside a higher risk of complications from any treatment undertaken. Methods: Retrospective cohort analysis was conducted on all patients presenting to University Hospital Limerick over the age of 80 presenting with STEMI between January 2012 and December 2017. Patient-level data was sourced from electronic and paper patient records. Standard Bayesian statistics were employed for analysis. Results: A total of 1, 268 patients presented with STEMI during this period. 172 (13.6%) were 80 years or older. Of this subgroup, 159/172 (92.4%) were true STEMI. 124/159 (77.9%) patients were brought to the catheterization lab and 35/159 (22%) were managed medically. 107/159 (67.29%) had angiographic evidence of acute total or partial thrombotic occlusion, and of these 97/107 were treated with PPCI (figure 1 ). Overall mortality at 1 year was 26.4% (42/159), and patients in the PPCI group had numerically lower 30 day mortality compared with the conservative group (20.6% vs 37.1% respectively, p=0.07). At one year follow-up, there was a significantly higher mortality observed in the conservative group versus the PPCI group (48.6% vs 22.4% respectively, p=0.005) (figure 2 ). Average length of stay for patients brought to catheterization laboratory was 5.53±8.2days. Of the patients brought to the cardiac catheterization laboratory (n=124), 16 patients (12.9%) exhibited cardiogenic shock, with 9 of these (56.25%) requiring intra-aortic balloon pump insertion. The presence of cardiogenic shock was associated with 87.5% mortality in those who were brought to the catheterization laboratory. In those who were brought for intervention, the mortality associated with cardiogenic shock was associated with a hazard ratio of 9.95 (95% CI 5.0061–19.7888, p=<0.00001). At discharge, a relatively small proportion of patients 6/105 (5.7%) admitted from home required discharge to a long-term nursing home placement. Conclusions: This study demonstrates that there is a high mortality rate with STEMI in those aged 80 years or above, however, patients who are treated with PPCI have a significantly lower mortality rate at 1-year. The incidence of STEMI in patients over the age of 80 is likely to continue to rise and this may prove challenging. PPCI remains the optimal treatment approach towards STEMI and this should not be biased based on age, however, interventionists will need to take into account patient suitability on a case-by case basis. Octogenarians who undergo angiography and PPCI as required have 77.6% survival at 1 year and a 92.4% likelihood of discharge to home; without need for long term nursing home care. Despite the advanced age-profile of this cohort, we suggest favorable outcomes in the absence of cardiogenic shock and left ventricular pump failure.